Multinational interest & development in Africa : establishing a people's economy - Bijaoui, Ilan (Palgrave Macmillan, 2017)
This book analyzes the current economic situations in African countries at the local, regional, and national level. It examines the growing interest from developed and developing countries to invest in Africa and their different reasons for doing so, which aren't always aligned with the interests of African countries. Growth in African GDP has benefitted mainly multinational corporations while the rest of the population remains at the subsistence level, creating a smaller middle class and less opportunity for local businesses to flourish. This book offers potential models of cooperation which could create added value for both African countries and the MNCs investing in them.